Elective Thoracoscopic Maze with Venoarterial Extracorporeal Life Support. Issue 5 (1st September 2015) - Stein, Erica J.; Elsenraat, Abram; Sirak, John H.; Mast, David; Gerhardt, Mark
Abstract : This case report describes the intraoperative use of extracorporeal life support (ECLS) for an elective thoracoscopic maze procedure in which the patient could not tolerate one-lung ventilation because of hypoxia. Potential pitfalls associated with the anesthetic management of elective intraoperative ECLS include managing native cardiac ejection and ECLS flows to provide optimal oxygenation and cardiac output. Particular attention must be paid to cardiac and respiratory physiology when ECLS is used in a patient with normal cardiac function.